Minimasi Waste pada proses produksi roti menggunakan metode value stream mapping dan 5S di UMKM Massempo Bakery - Nurjana, Anisa; Rasyid, Abdul; Uloli, Hendra (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study was conducted at UMKM Massempo Bakery with the aim of identifying and minimizing waste in its production process. Waste occurring during production can negatively impact efficiency and effectiveness, making improvements essential. The methods used in this research are Value Stream Mapping (VSM) and 5S. VSM was applied to map the value stream in the production process and identify existing wastes. The research findings revealed several types of waste, including defect, waiting, and motion. To minimize these wastes, improvements were made through the implementation of the 5S methodology, which includes Seiri (Sorting), Seiton (Set in Order), Seiso (Shining), Seiketsu (Standardizing), and Shitsuke (Sustaining). The implementation of 5S resulted in a more organized workspace, cleaner production areas, and a more efficient workflow, ultimately helping to reduce defects, shorten production times, and eliminate unnecessary motion.